Long recovery induced by short exercise-to-rest ratio and effort duration determine the influence of hypoxia during repeated cycling sprints to exhaustion - Antoine Raberin; Joakim Elmer; Sarah J. Willis; Thomas Richard; Gianluca Vernillo; F. Marcelo Iaia; Olivier Girard; Davide Malatesta; Grégoire P. Millet (Bern Open Publishing, 2023)
Introduction Repeated sprints exercise (RSE) performed in hypoxia (RSH) induce greater performance improvement than in normoxia (Brocherie et al., 2017). It has been previously argued that RSH efficiency depend on the oxidative-glycolytic balance which is influenced by sprint duration and exercise-to-rest-ratio (E:R). Indeed, we recently showed that long sprint duration (e.g. 20 s vs 10 s or 5 s) blunts the additional impact of hypoxia on RSH with a constant large E:R of 1:22. However, E:R also influence acute response to RSH. Therefore, this study aims to compare acute responses during RSE to exhaustion with a short E:R (1:6) in normoxia (RSN) and hypoxia (FiO2 = 0.13) and the same sprint durations (5, 10 or 20 s) previously used. Methods On separate visits, 10 active participants completed in random order three RSH and three RSN sessions to exhaustion on a cycle-ergometer (Excalibur Sport, Lode) with three sprint durations and a constant short E:R of 1:6 (5:30; 10:60 and 20:120). Vastus lateralis muscle de-reoxygenation (Oxymon, Artinis Medical Systems) and power output were continuously recorded. Lower limb and breathing discomfort, blood lactate, and ratings of perceived exertion were evaluated immediately after exhaustion. Results Number of sprints and peak power output were higher while blood lactate was lower (all p < 0.001) during 5:30 compared to 10:60 or 20:120. No condition or interaction effects were reported for blood lactate and exercise-related sensation. Blood lactate and muscle deoxyhemoglobin increase (p < 0.001) and total hemoglobin decrease (p = 0.002) during sprint were more pronounced when sprint duration increased (no hypoxia effect). Discussion Similar deoxygenation changes during recovery were reported in hypoxia compared to normoxia suggesting that 1:6 ratio and the associated long recovery period seemed to allow myoglobin O2 store restauration, even with a FiO2 = 13%. Sprint effort should be interspersed by incomplete recovery making impossible the full O2 reloading myoglobin and PCr resynthesis. The increase in blood lactate and the concomitant decrease in muscle oxygenation during sprint with longer duration confirmed a switch in the oxidative-glycolytic balance for energy supply. Since short exercise-to-rest ratio blunt hypoxic effect during RSH due to too long recovery period, hypoxia did not participate to the switch from oxidative to glycolytic energy supply. Conclusion During RSE to exhaustion, a short exercise-to-rest ratio (i.e., 1:6) blunts the specific psychophysiological responses induced by hypoxia, probably due to too long of recovery period. Manipulating effort duration rather than hypoxic exposure is preferable to alter both anaerobic energy system solicitation and power produced during repeated cycling sprints to exhaustion using a short exercise-to-rest ratio. References Brocherie, F., Girard, O., Faiss, R., & Millet, G. P. (2017). Effects of repeated-sprint training in hypoxia on sea-level performance: A meta-analysis. Sports Medicine, 47, 1651-1660. https://doi.org/10.1007/s40279-017-0685-3